CVD Graphene Electrode for Direct Electrochemical Detection of Double-Stranded DNA - Afrah Bardaoui; Asma Hammami; Rabiaa Elkarous; Mohamed Ali Aloui; Rania Oueslati; Olfa Messaoud; Diogo M. F. Santos; Radhouane Chtourou (Inorganics, 2023)
Understanding and regulating DNA interactions with solvents and redox-active centers opens up new possibilities for improving electrochemical signals and developing adequate biosensors. This work reports the development of a modified indium tin oxide (ITO) electrode by chemical vapor deposition (CVD) of graphene for the detection of double-stranded DNA. The modified electrode shows a better electrical conductivity than ITO, as confirmed by electrochemical impedance spectroscopy (EIS), where a drastic decrease in the charge–transfer resistance, Rct, from ~320 to ~60 Ω was observed. Sequences of double-stranded genomic DNA with a different number of base pairs are evaluated through differential pulse voltammetry (DPV), using ferri/ferrocyanide ([Fe(CN)6]3−/4−) as a mediator in the solution. Variations in the electrochemical response of the [Fe(CN)6]3−/4− probe are observed after introducing redox inactive double-stranded DNA ions. The redox-active [Fe(CN)6]3−/4− probe serves as a scaffold to bring DNA into the graphene-modified ITO electrode surface, provoking an increase in the current and a change in the potential when the number of base pairs increases. These results are confirmed by EIS, which shows a variation in the Rct. The calibration of DPV intensity and Rct vs. DNA base pairs (bps) number were linear in the 495–607 bps range. The proposed method could replace the nucleic acid gel electrophoresis technique to determine the presence of a DNA fragment and quantify its size.